Is The Fate and Protection of Women as Domestic Workers are Responsibility of The State? - Satryo Sasono; Gayatri Dyah Suprobowati; Fatih Afrisal Bagus Septiano; Delasari Krisda Putri (Universitas Sebelas Maret, 2025)
The issue of the protection of women and children in Indonesia is a strategic discussion considering the rampant cases of gender-based violence, domestic work as a profession that is mostly done by women and even children, and at the legal level, they must be protected by the state as mandated by the constitution to protect the entire community. The state is present as a mediator in this private sphere to protect children and women from the worst work, thus creating a socio-cultural society that cares about the slightest violence. What is needed is a legal construction that responds in terms of content, culture and structure. This paper uses a statutory approach, legal comparisons with several ASEAN countries and a conceptual approach. This research concludes that the legal vacuum for the protection of domestic workers gives the potential for wider gender violence even approaching TPPO (Trafficking in Persons), the Philippines is a good practice for the existence of the DW Bill and the establishment of a special monitoring unit for domestic workers facilitated by the state.